Le conflit ukrainien, des enjeux géopolitiques et géoéconomiques - Pascal Marchand (EchoGéo)
Ukrainian territory was drawed on the map in 1945, in an area of immemorial conflicts. This territory is gathering regions with very different history and memory. Geographical situation and soviet technological connections still ties russian en Ukrainian economies. In the future, EU and NATO will play a leading role in relations between the two countries.